Second Five Year Plan in Bihar A Review of Progress in the Second Year (1957-58) - Planning Commission (Planning Commission, 1957)
The Second Five-Year Plan for Bihar comprises of 418 schemes with a total outlay of Re. 190.2 crores. In the first year as many as 355 schemes were taken up with a total plan provision of Rs. 28.03 crores. During 1957-58, the year under review, 396 schemes were in progress. the total original outlay was Rs. 31.11 crores including Damodar Valley Corporation power and Kosi Irrigation. This had, however, to be reduced by the State Government in October, 1957 to Rs. 28.97 crores because of the need for extra funds for relief of distress caused by the widespread damage to the kharif crops due to the failure of rams in
Government of Bihar